An efficient approach to modulate the coordination number of yttrium ions for diverse network formation. Issue 28 (18th June 2019) - Park, Jiwon; Koo, Jin Young; Choi, Hee Cheul
Abstract : Hidden role of water! It acts as a key to determine the coordination number of yttrium by controlling the active ligand concentration. Abstract : Yttrium-based MOFs with different coordination numbers (CNs) of yttrium ions were synthesized from the same precursor. The 7-coordinated yttrium-based MOF exhibits an infinite 3D structure, while the 9-coordinated yttrium-based MOF shows a 2D layer stacked structure. Control experiments showed that the concentration of the ligand determines the CN and eventually the geometric structures.